2019
DOI: 10.1111/geer.12200
|View full text |Cite
|
Sign up to set email alerts
|

Did the German Minimum Wage Reform Influence (Un)employment Growth in 2015? Evidence from Regional Data

Abstract: Using the variation across space, age and sex and the variation across space and sectors, we analyse the relationship between the minimum wage and (un)employment growth in 2015. We use difference-in-differences specifications and instrument the bite of the minimum wage by the lagged bite. The results provide stable evidence that a higher minimum wage bite is related to a higher growth rate of regular employment. We also find stable evidence that a higher minimum wage bite is related to a lower growth rate of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 48 publications
7
61
3
Order By: Relevance
“…and concentrated among marginally employed workers (Caliendo et al 2018;Schmitz 2019). The finding that regular employment increased initially in response to the reform is in line with extant studies as well (Schmitz 2019;Garloff 2019). Interestingly, I find that the negative effect on marginal employment in East Germany has grown over time and was perhaps intensified by the 2017 increase of the minimum wage that was slightly higher than the inflation rate.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…and concentrated among marginally employed workers (Caliendo et al 2018;Schmitz 2019). The finding that regular employment increased initially in response to the reform is in line with extant studies as well (Schmitz 2019;Garloff 2019). Interestingly, I find that the negative effect on marginal employment in East Germany has grown over time and was perhaps intensified by the 2017 increase of the minimum wage that was slightly higher than the inflation rate.…”
Section: Resultssupporting
confidence: 86%
“…Concerning the German reform, previous studies found no discernible employment effects (Ahlfeldt et al 2018;Dustmann et al 2019) or at most moderately negative effects (Bossler/Gerner 2019;Caliendo et al 2018). Furthermore, some studies have identified a positive impact on regular employment, i. e. jobs that yield earnings above €450 per month, alongside a negative impact on marginal employment, i. e. jobs that pay below this threshold (Garloff 2019;Holtemoller/Pohle 2017;Schmitz 2019). Before the reform, economists warned that a universally set minimum wage might be too high and thus economically harmful for East Germany because wages there are considerably lower than in West Germany (Möller/König 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Employing an inter-regional comparison, Garloff (2016) and Ahlfeldt et al (2018) do not find evidence for disemployment effects using inter-regional variation in the minimum wage's marginal impact. Garloff (2016) further documents that employment requiring the payment of social security contributions increased strongest in regions where the number of mini jobs decreased the most. Bossler and Gerner (2016), on the other hand, find mild disemployment effects.…”
mentioning
confidence: 74%
“…The other two studies use variation in the regional bite of the minimum wage. While Garloff (2016) uses data from the Federal Employment Agency and a sample of prime age workers of age 30 to 54, Caliendo et al (2017) use the Structure of Earnings Survey (SES) 2014 combined with the SOEP. Both studies find either small or no negative effects of the minimum wage on full-time employment, and a significantly negative effect on marginal employment (a decrease of 180,000 jobs in the study by Caliendo et al).…”
Section: Brief Comparison To Existing Reduced-form Studiesmentioning
confidence: 99%
“…The few available ex-post analyses of the uniform minimum wage imposed in 2015 are provided by Bossler and Gerner (2016), Garloff (2016) and Caliendo et al (2017). These studies also rely on a difference-in-differences design and, in general, exploit variation in the minimum-wage bite at the regional or establishment-level for treatment assignment.…”
Section: Introductionmentioning
confidence: 99%